SARS-CoV-2/Covid-19 cambió el estilo de vida (REVISTA SAYWA, 2023)
In December 2019, the fi rst cases of respiratorydisease caused by an emerging coronaviruswere detected, which was called SARS-CoV-2,which in the fi rst months of 2020 spreadthroughout the world, for which the WorldOrganization of the health raised its status topandemic.The disease, known as Covid-19, occurs witha cough, fever and respiratory distress. Themost serious forms, which mainly affect theelderly and with certain comorbidities, are